2016
DOI: 10.1007/s00264-016-3344-7
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty with dual mobility cup in osteonecrosis of the femoral head in young patients: over ten years of follow-up

Abstract: Osteonecrosis of the femoral head affects mainly young patients with high functional needs this increases the risk of dislocation. Dual mobility cups known for low rate of dislocation and high mobility range seems indicated. We evaluate functional efficiency, survival and dislocation rate of dual mobility cup for total hip arthroplasty for osteonecrosis in young patients. Monocentric retrospective clinical study, from 2000 to 2008. With a clinical analysis in pre-operative and over ten years of follow-up of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 29 publications
4
19
0
1
Order By: Relevance
“…This study demonstrated no episode of dislocation and an excellent survivorship of 100% with a mean follow-up of 51 months. This is in line with the study of Martz et al (2017) who reported same survival rate at a mean follow-up of 109 months [ 8 ]. Similarly, no other major post-operative complications occurred in our series as well; there were no signs of implant loosening or peri-prosthetic osteolysis [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study demonstrated no episode of dislocation and an excellent survivorship of 100% with a mean follow-up of 51 months. This is in line with the study of Martz et al (2017) who reported same survival rate at a mean follow-up of 109 months [ 8 ]. Similarly, no other major post-operative complications occurred in our series as well; there were no signs of implant loosening or peri-prosthetic osteolysis [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…It has been also reported that dislocation is the most common cause of THA revision surgery during the first five years and those with ONFH had the highest risk for revision surgery [ 7 ]. Thus, it is critical to choose the appropriate THA implant for this population, which ensures stability, mobility, solidity, and longevity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical function and patient satisfaction were also excellent in this cohort. 41 A separate review by Assi et al corroborated these findings, with no dislocations and 100% implant survival at 4.25-year follow-up. 42…”
Section: Avascular Necrosis Of the Femoral Headmentioning
confidence: 82%
“…Good results are also established for specific categories of patients requiring a THA: those with femoralhead osteonecrosis [20], the obese [21], patients with high risk of dislocation (younger, active individuals) [22], or after hip fractures [23]. Regardless, taking in account the efficiency of DMC against instability, its use even with hip musculoskeletal oncology is emphasised by Zocalli et al [24].…”
mentioning
confidence: 99%